2013
DOI: 10.5713/ajas.2013.13200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single Cell Protein Replacing Fish Meal in Diet on Growth Performance, Nutrient Digestibility and Intestinal Morphology in Weaned Pigs

Abstract: Three experiments were conducted to evaluate the ME value, standardized ileal digestibility (SID) of amino acids (AA) of fish meal, and the effects of single cell protein (Prosin and Protide) replacing fish meal in diet on growth performance, nutrient digestibility and intestinal morphology in weaned piglets. In Exp. 1, twenty-four barrows with initial BW of 30.8±2.6 kg were allotted to one of four dietary treatments. Diet 1 contained corn as the only energy source. The other three diets replaced 20% of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
2
15
1
1
Order By: Relevance
“…Intestinal villi size is important for nutritional digestion and absorption as longer villi possess a larger surface area for absorption [29]. Bilić-Šobot et al [10] showed that supplementation of HT increased villus height and villus perimeter of the duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal villi size is important for nutritional digestion and absorption as longer villi possess a larger surface area for absorption [29]. Bilić-Šobot et al [10] showed that supplementation of HT increased villus height and villus perimeter of the duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…It contains crude protein (609 g CP · kg −1 dry matter (DM)), ether extract (79 g EE · kg −1 DM) and balanced amino acids. In comparison with fishmeal it is characterized by lower lysine content (Zhang et al, 2013). Zhang et al (2013) further reported that C. ammoniagenes-ABSTRACT.…”
Section: Introductionmentioning
confidence: 98%
“…In comparison with fishmeal it is characterized by lower lysine content (Zhang et al, 2013). Zhang et al (2013) further reported that C. ammoniagenes-ABSTRACT. In total six hundred, day-old Ross 308 male broiler chickens were fed one of four diets containing 0, 10, 30 or 50 g of Corynebacterium ammoniagenes-derived single cell protein (SCP) per kg for 35 days to investigate the effect of graded level of SCP on growth performance, organ weights, serum and tibia characteristics, and meat quality.…”
Section: Introductionmentioning
confidence: 98%
“…Feed ingredients of animal origin such as fish meal are therefore often used in diets fed to weanling pigs instead of soybean meal (Stoner et al, 1990;Kim and Easter, 2001). However, brewers' yeast or single-cell yeast protein may also be used in diets fed to weanling pigs (White et al, 2002;Zhang et al, 2013). Single-cell yeast protein may be produced using different technologies (Øverland and Skrede, 2012).…”
Section: Introductionmentioning
confidence: 99%